Pengaruh Tingkat Bagi Hasil Deposito Bank Syariah Dan Suku Bunga Deposito Bank Umum Terhadap Jumlah Simpanan Deposito Mudharabah(Studi Pada Bank Umum Syariah di Indonesia Periode 2010-2013) - Wahyuningtyas, Dika; , Drs. Agus Endro S, M.Si (2015)
Intention of this research to influence test of mount moslem bank deposit sharing holder to amount of mudharabah deposit and influence test of common/public bank deposit rate to amount of mudharabah deposit. This research use data of seconder coming from moslem banks website, with data in form of financial statement quarterly. Population in research that is counted 11 Bank. Research sample are determined with purposive sampling method. Sample in this research are 5 moslem of common/public bank in Indonesia. Analysis technique which is used in this research analysis of doubled linear regression. Pursuant to result of research at model of regression known by several things, the following: (1)variable moslem bank deposit sharing holder level have an effect on positive and statistically significant to amount of deposit of mudharabah, (2) common/public bank rate variable have an effect on negativity and statistically significant to amount of deposit of mudharabah.